CONSTRUCTION OF BICYCLIC GRAPH AND ITS APPLICATION IN TRANS JOGJA ROUTES - Ambarwati, Aditya; Krisnawati, Vira Hari (PATTIMURA UNIVERSITY, 2023)
A bicyclic graph is a type of graph that consists of exactly two cycles. A cycle is a graph that is a closed path where no vertices are repeated except the first and last vertices which are the same. The cycles in bicyclic graph can be of different lengths and shapes, but they must have at least one common vertex. Bicyclic graphs can be divided into two categories based on the types of induced subgraphs they contain. One category consists of graphs that include an -graph as an induced subgraph, while the other category comprises graphs that contain a -graph as an induced subgraph. There are 3 types of bicyclic graph without pendant vertex. A directed graph, also referred to as a digraph, is a graph in which each edge is assigned a specific direction. A directed bicyclic graph is a special kind of directed graph that contains precisely two distinct directed cycles. This graph can be applied in transportation problem. In this article, we give some examples of directed bicyclic graph in Trans Jogja routes.